Removal of Dyes from Wastewater of Textile Industries Using Activated Carbon and Activated Alumina - Taher Mohammed, Wadood; F. Farhood, Hasan; Hassoon Bjaiyah Al-Mas'udi, Abbas (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
This work was carried to study the capability of activated alumina from bauxite compared with activated carbon adsorption capability to reduce the color content from Al-Hilla Textile Company wastewater. Six dyes were studied from two types(reactive and dispersed) namely (blue, red, yellow) from wastewater and aqueous solutions.Forty eight experiments were carried out to study the effect of various initial conditions (bed height, flow rate, initial concentration, pH value, temperature, and competitive adsorption) on adsorption process.The results showed that the adsorption process using activated carbon insured a good degree of color reduction reaching (99.7%) and was better than activated bauxite which reached (95%).